1991
DOI: 10.2172/5670015
|View full text |Cite
|
Sign up to set email alerts
|

Single-shell tank constituent rankings for use in preparing waste characterization plans

Abstract: This effort is part of the initial exploratory characterization efforts for mixed wastes in underground single-shell tanks (SSTs) at the U.S. Department of Energy's (DOE) Hanford Site being conducted in accordance with DOE's waste characterization plan (Winterset al. 1g89). The purpose of this analysis was to provide a preliminary ranking of the constituents in the SST waste and provide information for use in establishing detection limits for the analytical characterization of the wastes. This report documents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…First, constituents of concern (COCs) were established from a risk standpoint. The COCs developed are presented in Table 1 and were primarily drawn from data in Droppo (1991). Droppo determined that constituents that resulted in a potential carcinogenic risk (R) greater than 1 .O E-06 or a non-carcinogen hazard index (HI) greater than 1 .O, based on the transport model used, were to be considered COCs.…”
Section: Allowable Leak Valuesmentioning
confidence: 99%
“…First, constituents of concern (COCs) were established from a risk standpoint. The COCs developed are presented in Table 1 and were primarily drawn from data in Droppo (1991). Droppo determined that constituents that resulted in a potential carcinogenic risk (R) greater than 1 .O E-06 or a non-carcinogen hazard index (HI) greater than 1 .O, based on the transport model used, were to be considered COCs.…”
Section: Allowable Leak Valuesmentioning
confidence: 99%
“…Unit risk factors were generated using the Multimedia Environmental Pollutant Assessment System (MEPAS) Application Guidance (Buck et al 1995) for each contaminant of concern. A unit transport factor was estimated for a single "unit" source (e.g., curie, gram,) of each contaminant, in (a) See, for example, the Hanford Defense Waste EIS (DOE 1987), Droppo et al (1991), Buck et al (1991), Kincaid (1994), Wood (1994), and Napier (1995).…”
Section: -U-235 and 238mentioning
confidence: 99%
“…In general, these standard represent a high level of risk reduction. However, for the Hanford tank wastes, several assessments (Droppo et al 1991;Buck et al 1991) have indicated that, if not retained within the disposal system, Tc-99, 1-129, and U-238 are primary contributors to long-term radioactivity-related risk even at concentrations allowed by the Class A limit. Thus, the clean option goals include an additional reduction for these constituents.…”
Section: Assumptions and Rationale For Selection Of Goalsmentioning
confidence: 99%